Facebook, Friends, and Fear - Baumgart, Tyler; Edlund, Sarah; Mather, Shelley; Michaels, Nicole (My University, 2012)
The purpose of this study was to expand on the research of social networking that has already been done. This research focused primarily on barriers, apprehensions, and gratifications relative to Facebook.
Color poster with text and tables.
Keywords: Facebook (Electronic resource); Online social networks; Fear--Social aspects; Posters